Tata Kelola Rantai Nilai Sayuran Daun Hidroponik Di Wilayah Bogor (Forum Agribisnis, 2025)
Value chain governance within hydroponic systems plays a critical role in optimizing every stage, from product design to marketing. This study aims to analyze the governance structure established in the value chain of hydroponic leaf vegetables. Primary data were collected through structured interviews using questionnaires and field observations. The sampling method employed was snowball sampling, involving a total of 9 farmers, 2 collectors, and 1 retailer as respondents. Data analysis was conducted qualitatively using a descriptive approach, referring to the value chain analysis framework proposed by Kaplinsky. The findings reveal that the type of governance in the hydroponic leaf vegetable value chain in Bogor Regency is categorized as modular governance. This governance type reflects a high degree of independence among actors within the value chain, coupled with strong coordination and adherence to established standards. These results provide insights into the efficiency and adaptability of modular governance in supporting sustainable and technologically driven agricultural practices.